Fulminant Neisseria meningitidis septicaemia with purpura fulminans requiring limb amputation. (2020) - Davies, H.; Pannu, K.; Edwards, J.; Pittman, M.; Mukherjee, D.
Abstract: Despite the isolation of Neisseria meningitidis over 200 years ago, meningococcal disease remains a feared cause of bacterial sepsis, with significant morbidity and mortality, despite prompt antibiotic use and modern critical care support. Neisseria meningitides is a Gram-negative encapsulated diplococcus, which exists only in the human host (Kvalsvig and Unsworth, 2003). The bacterium can cause life-threatening septic shock and coagulopathy, which may rapidly manifest within a matter of hours from preceding mild symptoms (Kvalsvig and Unsworth, 2003). Whilst N. meningitidis is recognised as a common commensal organism in the nasopharynx, associated with asymptomatic carriage in up to 10 %, manifestation of life-threatening disease is rare (Rappuoli and Pizza, 2015). We report the case of 31-year-old male presenting with devastating meningococcal septicaemia with disseminated intravascular coagulopathy (DIC) and purpura fulminans, requiring surgical debridement and a right above-knee amputation for sepsis-driven skin necrosis. The patient suffered extensive tissue loss secondary to a type 3 immune hypersensitivity reaction involving immune-complex mediated inflammation and tissue necrosis. Due to a strong immune component driving the patient's failure to convalesce pulsed intravenous methylprednisolone was used alongside antimicrobial therapy. The use of steroids was associated with fever subsidence and significant clinical improvement, highlighting the benefit of corticosteroid use in immune-complex mediated pathology.